Free Sky and Clouds of Restrictions - Roberta Piermartini; Linda Rousova (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
An increasing percentage of trade occurs via air. However, air services are excluded from the WTO Agreement and, as a result, the aviation market is regulated by a plethora of Air Services Agreements. In this paper, we investigate the extent of discrimination -in terms of access to international air services- generated by this system. In particular, using recently available information on Air Services Agreements for 184 countries, we estimate the impact of international air services liberalization on air passenger flows. We find that increasing the degree of liberalization has a positive and significant effect. For instance, the higher degree of air services liberalization among countries of the European Economic Area (EEA) is estimated to account for approximately 30 per cent higher intra-EEA passenger traffic compared with countries that signed Open Skies-type agreements. Our results are robust to the use of several measures of liberalization as well as alternative estimation techniques that address potential problems of endogeneity, heteroscedasticity and data inaccuracy.
urn:nbn:de:bvb:19-epub-10944-2
Keywords: F15; L93; R48; 330; Air Services Agreements; Air services liberalization; Air passenger traffic; Regulatory quality.; Luftverkehr; Dienstleistungshandel; Protektionismus; Handelsliberalisierung; Deregulierung; Wirkungsanalyse; Passagierluftfahrt; EWR-Staaten